Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Financial Safety Nets-Managing Problem Banks and Systemic Banking Crises. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the Netherlands in the areas of managing problem banks and systemic banking crises. Significant progress has been made toward implementing the Banking Union, although key aspects have not yet been completed. The Single Resolution Board (SRB), which assumed responsibility in January 2016, remains in start-up mode, and the Dutch central bank provides substantial support to Dutch banks. Another challenge is the complex decision-making structure of the SRB, which may impede timely decision making when it comes to resolution. The adequacy of financial safety nets remains a concern.